A Bottom-Up Proteomic Approach in Bone Marrow Plasma Cells of Newly Diagnosed Multiple Myeloma Patients - Ayhan, Beycan; Turan, Seçil K.; Barkan, N. Pınar; Dalva, Klara; Beksaç, Meral; Demiralp, Duygu Özel (Current Proteomics, 2021)
Background: Multiple myeloma (MM) is characterized by infiltration of bone marrow (BM) with clonal malignant plasma cells. The percentage of plasma cells in the BM is required for both diagnosis and prognosis. Objective: Intracellular protein screening and quantitative proteomic analysis were performed in myeloma plasma cells with an aim to compare expressions between low (0-9%), intermediate (10-20%) and high (>20%) plasma cell infiltration groups. Methods: BM aspiration samples were collected from newly diagnosed untreated patients with MM. The samples were pooled into three groups according to the plasma cell content (PCC) in the BM: group 1 (0-9%), group 2 (10-20%) and group 3 (>20%). Protein profiles were obtained and proteins were identified by peptide mass fingerprinting analysis. Results: Differentially expressed proteins were detected between all groups. The identified proteins are Endoplasmin, Calreticulin, Protein Disulfide-isomerase, Marginal zone B and B1 cell specific protein/pERp1, Actin cytoplasmic 1, Myeloblastin, Thioredoxin domain-containing protein 5, Ig kappa chain C region, Apoptosis regulator B-cell lymphoma 2 and Peroxiredoxin-4. Conclusion: Proteins involved in cell proliferation, apoptosis, redox homeostasis and unfolded protein disposal through endoplasmic reticulum-associated degradation machinery have been found to be correlated to PCC. Our results confirm earlier reports regarding the potential effects of identified proteins in the major signaling pathways that lead to cancer. Moreover, this study reveals a novel association between PCC levels and MM. It further highlights the roles of Marginal zone B and B1 cell specific proteins in MM, which could be used as candidate biomarkers in future studies.
Keywords: Bone marrow